ANALISIS KEBIJAKAN TIONGKOK TERHADAP PERKEMBANGAN CRYPTOCURRENCY - Prasetya, Nanda Eka; Susiatiningsih, Hermini (Journal of International Relations, 2019)
The development of financial technology arrived at a new form, i.e. cryptocurrency. Cryptocurrency development with an increasingly widespread network and its autonomous nature cannot be controlled by the state, which makes China took a policy to block all domestic cryptocurrency activities. The policy became unnatural when China occupies the top position in the emerging global cryptocurrency market. The anomaly is interesting to study further to find a motivating reason for China to take a firm policy while it is in a safe position as a center for global cryptocurrency production and transactions. In order to explain these reasons, the theory of national interest and rational choice are used as the main tool in analyzing the issue. The theory of national interest and rational choice explains that the policy taken by China is motivated by the economic and security interests, as well as the rational calculation of the advantages and disadvantages of that policy